Global Production Networks in Electronics and Intra-Asian Trade - Byron Gangnes; Ari Van Assche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
The growth of East Asia's intra-regional trade is driven largely by increased component trade within global electronics production networks. Data on both electronics trade and production elucidate a pattern of specialization in which upper- and middle-income countries produce sophisticated components and lower-income countries assemble lowervalue- added final goods. There is evidence of increasing sophistication within the electronics sector by the Newly Industrialized Economies and to a lesser extent by ASEAN countries. Despite the marked increase in intra-regional trade, developing East Asian countries remain heavily dependent on developed-country markets. When Western export demand rapidly contracted during the 2008-2009 economic crisis, these specialization patterns led the rapid diffusion of the business cycle shock throughout the East Asian region.
Keywords: F14; F23; F40; L63; 330; Global production networks; electronics; Asian trade; business cycle transmission; global economic crisis; Elektronikindustrie; Internationale Produktion; Unternehmensnetzwerk; Konjunkturzusammenhang; Handelsregionalismus; Wirtschaftskrise; Ostasien